Does exchange rate volatility matter for the balancing item of balance of payments accounts in Japan? : An empirical note - Tang, T.C. (Cedam Casa Editrice Dott Antonio Milani, 2005)
This study provides preliminary empirical support on the impact of exchange rate volatility on Japan’s balancing item using subset VAR (Vector Autoregression) approach although small. The finding of this study adds an empirical dimension on the trade literature, particularly for Japan, and opens a door for further debate.